Steel for large-size anchor chain shackle and production method thereof
By using specific chemical composition and fine smelting processes in the steel for anchor chain shackles, the problem of insufficient performance of traditional steel under complex sea conditions is solved, and a large-scale anchor chain shackle steel with high strength, high impact toughness and wear resistance is achieved, extending the service life and improving cost-effectiveness.
Patent Information
- Application Number
- CN202510087445.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing steel for anchor chain shackles cannot meet the demand for high-performance anchor chain shackles in large-scale marine ships and marine engineering. Especially under complex sea conditions, traditional steels have shortcomings in high strength, high impact toughness and wear resistance.
The steel for large-scale anchor chain shackles with specific chemical compositions, including C, Si, Mn, Cr, Mo, V, Nb, Al and other elements, is controlled through fine smelting processes such as converter coarse refining, LF furnace refining and RH vacuum treatment, and the composition and structure of the steel are improved to improve its mechanical properties.
It realizes the high strength, high impact toughness and wear resistance of anchor chain shackles, extends the service life, and achieves a high cost-effectiveness in low-temperature impact work and non-metallic inclusion control, completely replacing existing products.
Smart Images

Figure CN119530672A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to steel for large-size anchor chain shackles and a production method thereof, and belongs to the manufacturing field of large-size anchor chain shackles for ships and marine engineering. Background Art
[0002] The anchor chain is connected to the anchor through a connecting ring, and the chains are also connected through connecting rings. This connecting ring is called a shackle, and the anchor chain shackle is the most common connecting ring for ships and marine engineering. For marine ships, offshore wind power generation, offshore buoy mooring, deep-sea scientific research, etc., they are inseparable from the anchor chain shackle. Generally, an anchor chain consists of several "sections", each section is 27.5m long, and each section of the anchor chain is connected by an anchor chain shackle. At the same time, the anchor chain shackle can also be used to connect the anchor chain to the anchor. The anchor chain shackle, chain link and anchor form a whole. The anchor chain shackle is the same as the anchor chain. In addition to the quality requirements of the chain link itself, the quality requirements for the anchor chain shackle are higher. They are all "safety buckles" to ensure ships and marine engineering.
[0003] As ocean transport ships, cruise ships and ocean-related projects gradually develop towards large-scale, especially ship transport, due to market competition, increasing the single cargo volume of transport ships can relatively reduce the transportation cost of unit cargo, which requires that the transport ships be large enough. It can be seen that the large-scale transport ships have become an inevitable trend in the development of the industry. Under the background of the development of large-scale ocean ships, cruise ships and ocean engineering, the matching anchor chain shackles must also require larger specifications (≥Ø180mm). Due to the harsh use environment of the anchor chain shackle, the collision between the anchor chain and the shackle, the shackle and the anchor, and the alternating load and impact load of the anchor chain shackle, the anchor chain shackle is required to have very high strength, high impact toughness and wear resistance.
[0004] At present, the existing technologies about anchor chain shackles at home and abroad mainly focus on the structural design and processing methods of anchor chain shackles, such as the utility model with application number 202420004525.1 provides an anchor detachment shackle, the utility model with application number 202322638457.2 provides a U-shaped connecting shackle for reinforcing navigation mark, the utility model with application number 202220461680.7 provides a high-strength D-type shackle, the utility model with application number 202320870276.X provides a new type of buoy anchor chain shackle, the utility model with application number 202221037342.7 provides a high-strength anchor chain shackle, and the invention with application number 201780025195.7 provides a Kent shackle. The above-mentioned utilities have made relevant improvements in the structure of the shackle. The invention with application number 201911179515.1 provides a manufacturing process for an R6-grade Kent shackle, the invention with application number 201610366506.3 provides a manufacturing method for a double-nut D-connecting shackle, and the invention with application number 201911179551.8 provides an anti-fatigue R6 connecting shackle and its forging method. The manufacturing methods provided above are only improvements made to the processing technology of the shackle to improve the convenience and extensiveness of the use of the shackle. Obviously, the above structural design and processing have relatively little effect on the performance of the shackle. The improvement of performance requires the design of chemical composition. In the invention with application number 202010112278.3, a steel for a D-type anchor chain shackle is introduced, but it only provides the design of chemical composition and does not provide the corresponding production process method. Therefore, the actual impact energy of the patent is only 64J when the specification is larger.
[0005] As the working environment of anchor chain shackles becomes increasingly harsh, the 30Mn2 steel used in traditional anchor chain shackles can no longer meet the high performance requirements of shackles for large-scale marine ships and marine engineering. Therefore, it is urgent to develop a steel for anchor chain shackles suitable for complex sea conditions. Summary of the invention
[0006] The invention provides a large-size anchor chain shackle steel and a production method thereof, takes the mechanical properties and processing technology of the large-size anchor chain shackle as the design goal, solves the shortcomings of the existing anchor chain shackle in steel technology and the difficult problems that restrict the development of marine transportation and marine engineering.
[0007] The technical solution adopted by the present invention to solve its technical problem is: A steel for large-size anchor chain shackle, for steel grades used for processing large-size anchor chain shackles with a diameter of Ø≥180mm, comprising the following elements in mass percentage: C: 0.34-0.38%, Si: 0.05-0.12%, Mn: 1.58-1.68%, Cr: 0.56-0.65%, Cu≤0.10%, Ni≤0.08%, Mo: 0.035-0.045%, V: 0.050 -0.070%, Nb≤0.0080%, As≤0.0050%, Al: 0.005-0.020%, P≤0.018%, S≤0.005%, B≤0.0006%, Ti≤0.0050%, N: 0.0060-0.080%, [O]≤20ppm, [H]≤2ppm, the balance is Fe and unavoidable impurity elements; Cr / Mo is controlled at 12-19; Furthermore, if the diameter of the steel used for processing large-size anchor chain shackles is 180mm≤Ø≤240mm, it includes the following elements in mass percentage: C: 0.36-0.38%, Si: 0.05-0.12%, Mn: 1.58-1.64%, Cr: 0.56-0.60%, Cu≤0.10%, Ni≤0.08%, Mo: 0.035-0.045%, V: 0.050 -0.060%, Nb≤0.0080%, As≤0.0050%, Al: 0.005-0.020%, P≤0.018%, S≤0.005%, B≤0.0006%, Ti≤0.0050%, N: 0.0060-0.080%, [O]≤20ppm, [H]≤2ppm, the balance is Fe and unavoidable impurity elements; Cr / Mo is controlled at 12-18; Furthermore, if the diameter of the steel used for processing large-size anchor chain shackles is 180mm<Ø≤270mm, it includes the following elements in mass percentage: C: 0.34-0.37%, Si: 0.05-0.12%, Mn: 1.62-1.67%, Cr: 0.58-0.63%, Cu≤0.10%, Ni≤0.08%, Mo: 0.035-0.045%, V: 0.055 -0.065%, Nb≤0.0080%, As≤0.0050%, Al: 0.005-0.020%, P≤0.018%, S≤0.005%, B≤0.0006%, Ti≤0.0050%, N: 0.0060-0.080%, [O]≤20ppm, [H]≤2ppm, the balance is Fe and unavoidable impurity elements; Cr / Mo is controlled at 12-18; Furthermore, if the diameter of the steel used for processing large-size anchor chain shackles is 270mm<Ø≤300mm, it includes the following elements in mass percentage: C: 0.34-0.36%, Si: 0.05-0.12%, Mn: 1.63-1.68%, Cr: 0.60-0.65%, Cu≤0.10%, Ni≤0.08%, Mo: 0.035-0.045%, V: 0.060 -0.070%, Nb≤0.0080%, As≤0.0050%, Al: 0.005-0.020%, P≤0.018%, S≤0.005%, B≤0.0006%, Ti≤0.0050%, N: 0.0060-0.080%, [O]≤20ppm, [H]≤2ppm, the balance is Fe and unavoidable impurity elements; Cr / Mo is controlled at 13-19; The production method of large-size anchor chain shackle steel specifically comprises the following steps: Step S1: pretreatment of molten iron: mechanical stirring is used to pretreatment the molten iron for desulfurization. After starting the stirring for 1 minute, a desulfurizer is added to the molten iron. The sulfur content after pretreatment is ≤0.005%, and the desulfurization slag is scraped off; Step S2: rough refining in a converter, adding high-quality scrap steel to the molten iron pretreated in step S1, the smelting end point includes the following elements in mass percentage: C ≥ 0.10%, P ≤ 0.018%, and the temperature when tapping is 1610°C-1650°C; Deoxidizers of different proportions are added to the molten steel at different stages of steel tapping to deoxidize the molten steel; lime and pre-melted refined slag are added during steel tapping to remove inclusions in the molten steel; Step S3: LF furnace refining, hoisting the ladle into the LF furnace smelting station, starting the ladle bottom blowing argon stirring, setting the stirring time, after the stirring is completed, the LF furnace is powered on for smelting, setting the smelting time, if the aluminum content in the molten iron is less than 0.015%, feeding aluminum wire into the molten steel, after the first sampling aluminum content is within the range of 0.015%-0.030%, throwing a deoxidizer on the slag surface of the ladle, the deoxidizer is a mixture of calcium carbide and low-nitrogen carbon powder; after the second sampling, continue to throw a deoxidizer on the slag surface of the ladle, the deoxidizer is high-purity silicon carbide; Step S4: RH vacuum treatment, reducing the vacuum degree to within a preset range, continuing the treatment for a preset time, feeding nitrogen-manganese wire into the molten steel, and performing soft blowing at the same time; Step S5: continuous casting, the whole process is protected, the superheat range is set to 20-35°C, and the ratio of the amount of cold water and the electromagnetic stirring current of the crystallizer is controlled; after the steel billet is cast, it is slowly cooled in the pit, and the exit temperature is set to ≤100°C; Step S6: rolling, the steel billet after slow cooling in step S5 is put into the furnace for rolling, the heating temperature is set to 1180-1210°C, the steel billet after rolling continues to be slowly cooled in the pit, and the exit temperature is set to ≤100°C; Furthermore, in step S2, different proportions of deoxidizer are added to the molten steel at different stages of steel tapping to deoxidize the molten steel. Specifically, after 1 / 6 of the steel is tapped, aluminum particles and carbon powder are added to the molten steel. At this time, by mass percentage, aluminum particles: carbon powder = 1:5; After 1 / 2 of the steel is tapped, aluminum particles, carbon powder and metallic manganese are added to the molten steel. At this time, the mass percentage of aluminum particles: carbon powder is 6:2; After 5 / 6 of the steel is tapped, lime and pre-melted refined slag are added to the molten steel. The amount of lime added is 4-5 kg / t, and the amount of pre-melted refined slag added is 3.5-4.5 kg / t. Further, in step S3, after the ladle is hoisted into the LF furnace smelting station, argon blowing at the bottom of the ladle is started for stirring, and the stirring time lasts for 3 minutes. After the stirring is completed, the LF furnace is powered on for 6-10 minutes for smelting; after the first sampling, the deoxidizer added is a mixture of calcium carbide and low-nitrogen carbon powder, and in terms of mass percentage, calcium carbide: low-nitrogen carbon powder = 5:1; the entire LF refining time is controlled to be 40-50 minutes; Further, in step S4, within 5 minutes of vacuum treatment, the vacuum degree is reduced to 60-80 Pa, and the treatment is carried out at this vacuum degree for 18 minutes; after the vacuum treatment, 60-100 m nitrogen-manganese wire is fed into the molten steel, and the soft blowing time is controlled at 15-20 minutes; Further, in step S5, when the overheating range is 20-35°C, the ratio of the amount of cold water to the electromagnetic stirring current of the crystallizer is greater than 1:14, and the temperature of the cast steel billet when entering the pit for slow cooling is set to 650-720°C; Furthermore, the steel type produced by the production method for processing large-size anchor chain shackles has a lower yield strength of 608-650Mpa, a tensile strength of 750-790Mpa, an elongation of 22.3-25%, a cross-sectional shrinkage of 67-72%, a 0°C V-type impact energy of 118-162J, and non-metallic inclusions of Class A ≤0.5 level, Class B ≤0.5 level, Class D ≤1.0 level, and Class C is 0 level.
[0008] Through the above technical solution, compared with the prior art, the present invention has the following beneficial effects: 1. The large-size anchor chain shackle steel provided by the present invention adopts different ranges in component design according to different diameter specifications of steel grades used for processing anchor chain shackles, so as to achieve the best cost performance; 2. The steel for large-size anchor chain shackles provided by the present invention is designed for the first time with Cr / Mo in composition for the working condition of processing large-size anchor chain shackles with a diameter of Ø≥180mm, so as to improve the temper brittleness of large-size anchor chain shackles within the range of 2 / 3 radius to the core during the tempering process; 3. The production method of large-size anchor chain shackle steel provided by the present invention limits the mass percentage content of aluminum element in the refining stage, abandons the traditional method of using aluminum element for grain refinement, breaks the traditional situation of limiting nitrogen in anchor chains and anchor chain shackles, and adopts vanadium nitrogen to refine grains, thereby improving the performance of steel and further extending the service life of anchor chain shackles; 4. The production method of large-size anchor chain shackle steel provided by the present invention adopts a strong and weak mixed deoxidation method when tapping the converter and a weak deoxidation method in the refining stage, which effectively controls the generation of Class B inclusions. In the continuous casting stage, the relationship between cold water and electromagnetic stirring current is used for the first time to control segregation, etc., effectively achieving uniform and stable organization and performance, especially low-temperature impact energy, so that the steel has a higher cost performance and can completely replace existing products. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0010] Figure 1 is a diagram of non-metallic inclusions in Example 1 provided by the present invention; Figure 2 is a diagram of non-metallic inclusions in Example 2 provided by the present invention; Figure 3 It is a diagram of non-metallic inclusions in Example 3 provided by the present invention. DETAILED DESCRIPTION
[0011] The present invention will now be described in further detail with reference to the accompanying drawings. The specific dimensions used in this embodiment are only for illustrating the technical solution and do not limit the protection scope of the present invention.
[0012] In the background technology, the applicant elaborated in detail on the existing working conditions of the anchor chain shackle. In the face of complex sea conditions, anchor chain shackles that match marine ships, tankers and marine engineering are needed, that is, the anchor chain shackle is required to have high strength, high impact toughness and high wear resistance under the collision between the anchor chain and the shackle, the shackle and the anchor, the alternating load and the impact load of the anchor chain shackle. Obviously, only partially updating the structure and manufacturing process of the shackle can no longer meet the existing needs.
[0013] The present application provides a large-size anchor chain shackle steel and a production method thereof. In view of the mechanical property requirements of the large-size anchor chain shackle, the chemical composition of the steel used for processing the large-size anchor chain shackle and the smelting method are designed at the same time, so that the produced shackle can replace the existing products with relatively low performance.
[0014] As the first innovation of this application, the anchor chain shackle with a diameter of Ø≥180mm is relatively large. Therefore, in the design of steel composition, a medium-carbon design concept is adopted to ensure strength while also having low toughness and plasticity, especially low-temperature toughness.
[0015] Specifically, for steel grades with a diameter of Ø≥180mm used for processing large-size anchor chain shackles, the steel grades include the following elements in mass percentage: C: 0.34-0.38%, Si: 0.05-0.12%, Mn: 1.58-1.68%, Cr: 0.56-0.65%, Cu≤0.10%, Ni≤0.08%, Mo: 0.035-0.045%, V: 0.050-0.070%, Nb≤0.0080%, As≤0.0050%, Al: 0.005-0.020%, P≤0.018%, S≤0.005%, B≤0.0006%, Ti≤0.0050%, N: 0.0060-0.080%, [O]≤20ppm, [H]≤2ppm, and the balance is Fe and unavoidable impurity elements.
[0016] The reasons for the mass percentage restrictions of the above elements are explained below. First, element C. Among the chemical composition of steel, C has the most direct impact on the strength, hardness, plasticity and toughness of steel and welding performance. When the C content is ≤0.77%, with the increase of C content, the strength and hardness increase, and the plasticity and toughness decrease. At the same time, high C content will also have a very adverse effect on welding performance. Considering the requirements of anchor chain shackles in low temperature impact energy (generally, classification societies require 0℃ V-type impact energy ≥60J), the C content should not exceed 0.40% when designing. Therefore, the C content is 0.34-0.38%.
[0017] Element Si can promote the coarsening of ferrite grains during heating. In manganese-containing steel, silicon can increase the temper brittleness of steel. At the same time, Si will also promote the occurrence of surface decarburization of steel, increase the brittle transition temperature of steel, and reduce the welding performance of steel. Based on this, Si is strictly limited in the chemical composition design to avoid its adverse effects. In the patent of this invention, the Si content is controlled in a relatively low range, and the Si content is determined to be 0.05-0.12%.
[0018] Element Mn, Mn is a good deoxidizer and desulfurizer, which can eliminate or reduce the harm caused by sulfur, thereby improving the hot working performance of steel. It is well known that when the content of Mn element does not exceed 1.80%, the influence on the two aspects of strength and toughness is basically the same. Mn plays a role in refining pearlite in steel by reducing the critical transition temperature. Mn can also significantly improve the hardenability of steel, but when the Mn content is high, it is easy to coarsen the grains and increase the temper brittleness of steel. Mn also strongly increases the content of retained austenite in quenched steel. In the present invention, Mn is used as the main alloying element, so the Mn content is determined to be 1.58-1.68%.
[0019] Element Mo, Mo can significantly improve the hardenability of steel. Its effect on improving hardenability is stronger than Cr, but weaker than Mn. It improves thermal strength and prevents temper brittleness. Since Mn and Cr are added in the chemical composition design of this application, the addition of Mo is mainly used to improve the hardenability of steel, while inhibiting the temper brittleness caused by Cr and Mn, and improving the steel's resistance to temper brittleness or tempering stability. Mo is a strong carbide-forming element. Because the quenching medium of the anchor chain shackle is water, the product specifications of this application are relatively large. If the Mo content is high, cracking will occur in the subsequent quenching. For this reason, the added Mo content must be controlled. Based on the above reasons, the Mo content is determined to be 0.035-0.045%.
[0020] Element V, V mainly exists in the form of carbides and nitrides in steel, is used to refine the structure and grains, can improve the welding performance of steel, increase the tempering stability of steel, and produce secondary hardening, improve wear resistance, but the V content should not be too high, otherwise the dispersion and precipitation of V4C3 in the crystal will lead to a decrease in the toughness of the steel. The V content is determined to be 0.050-0.070%.
[0021] Element N, usually N is considered as an impurity element in steel and is controlled, but this application intentionally adds a small amount of N to play the role of V, but the N content should not be too high, otherwise it will combine with aluminum to form excess aluminum nitride, which will deteriorate the grain boundary. The N content is determined to be 0.0060-0.080%.
[0022] Element Nb and element Ti, traditionally Ti and Nb are added to steel, mainly for grain refinement, but in this application, a small amount of N element is added to minimize the influence of B element on mechanical properties after quenching and tempering, and in order to prevent the added N from combining with Ti and Nb to form angular nitride inclusions, this application prohibits the addition of alloys and auxiliary materials containing Ti and Nb to steel. Therefore, B≤0.0006%, Ti≤0.0050% are designed.
[0023] Element Al, in the steel of this application, aluminum is mainly used to control the oxygen content in molten steel, but considering that aluminum nitride weakens the grain boundary during continuous casting, aluminum is controlled at a relatively low content. Taking all factors into consideration, the Al content is designed to be 0.005-0.020%.
[0024] In order to ensure the stability of mechanical properties after tempering, Ni, Cu, P, S, B, As, [O], and [H] are all controlled as residual elements. The residual content requirements are: Ni≤0.08%, Cu≤0.10%, P≤0.018%, S≤0.005%, As≤0.0050%, [O]≤20ppm, [H]≤2ppm, especially for the control of residual B element content, B is set to 0.0006%.
[0025] During the tempering process, the anchor chain shackle often has temper brittleness from 2 / 3 radius to the core. Traditionally, it is only known that the element Mo can inhibit the temper brittleness of Cr, but how to effectively inhibit the temper brittleness of Cr has not been specifically given. Only by adding a certain amount of Mo element, after several studies and analyses, the applicant found that reasonable control of Cr / Mo can effectively inhibit the temper brittleness of Cr, and can also have a certain inhibitory effect on the temper brittleness of Mn. Therefore, in the composition design, for the first time, the range of Cr / Mo is limited to control the development degree of brittleness of the anchor chain shackle during the tempering process. Preferably, Cr / Mo is controlled at 12-19.
[0026] In actual working conditions, large-size anchor chain shackle steel with a diameter of Ø≥180mm can be further refined into three specifications: 180mm≤Ø≤240mm, 180mm<Ø≤270mm, and 270mm<Ø≤300mm. Therefore, in order to achieve the best cost-effectiveness, this application designs different composition ranges according to different specifications.
[0027] If the diameter of the steel used to process large-size anchor chain shackles is 180mm≤Ø≤240mm, it includes the following elements in mass percentage: C: 0.36-0.38%, Si: 0.05-0.12%, Mn: 1.58-1.64%, Cr: 0.56-0.60%, Cu≤0.10%, Ni≤0.08%, Mo: 0.035-0.045%, V: 0.050-0.060%, Nb≤0.0080%, As≤0.0050%, Al: 0.005-0.020%, P≤0.018%, S≤0.005%, B≤0.0006%, Ti≤0.0050%, N: 0.0060-0.080%, [O]≤20ppm, [H]≤2ppm, the balance is Fe and unavoidable impurity elements; Cr / Mo is controlled at 12-18.
[0028] If the diameter of the steel used to process large-size anchor chain shackles is 180mm<Ø≤270mm, it includes the following elements in mass percentage: C: 0.34-0.37%, Si: 0.05-0.12%, Mn: 1.62-1.67%, Cr: 0.58-0.63%, Cu≤0.10%, Ni≤0.08%, Mo: 0.035-0.045%, V: 0.055-0.065%, Nb≤0.0080%, As≤0.0050%, Al: 0.005-0.020%, P≤0.018%, S≤0.005%, B≤0.0006%, Ti≤0.0050%, N: 0.0060-0.080%, [O]≤20ppm, [H]≤2ppm, the balance is Fe and unavoidable impurity elements; Cr / Mo is controlled at 12-18.
[0029] If the diameter of the steel used to process large-size anchor chain shackles is 270mm<Ø≤300mm, it includes the following elements in mass percentage: C: 0.34-0.36%, Si: 0.05-0.12%, Mn: 1.63-1.68%, Cr: 0.60-0.65%, Cu≤0.10%, Ni≤0.08%, Mo: 0.035-0.045%, V: 0.060-0.070%, Nb≤0.0080%, As≤0.0050%, Al: 0.005-0.020%, P≤0.018%, S≤0.005%, B≤0.0006%, Ti≤0.0050%, N: 0.0060-0.080%, [O]≤20ppm, [H]≤2ppm, the balance is Fe and unavoidable impurity elements; Cr / Mo is controlled at 13-19.
[0030] On the basis of the above-mentioned composition design, the present application further provides a method for producing the large-size anchor chain shackle steel, which can improve the purity of the molten steel as much as possible, especially control the generation of alumina-type brittle inclusions, so as to meet the requirements of high strength, high impact toughness and high wear resistance.
[0031] The specific steps include: Step S1: pretreatment of molten iron: mechanical stirring is used to pretreat the molten iron for desulfurization. After starting the stirring for 1 minute, a desulfurizer is added to the molten iron. The sulfur content after pretreatment is ≤0.005%. After desulfurization, the desulfurization slag is scraped off.
[0032] Step S2: Rough refining in a converter, adding high-quality scrap steel to the molten iron pretreated in step S1 (the high-quality scrap steel here is the scrap steel produced in the steelmaking plant, the quality of the scrap steel produced in the plant is guaranteed, it can reduce the introduction of impurities and improve the quality of steel), the smelting end point includes the following elements in mass percentage: C ≥ 0.10%, P ≤ 0.018%, here, carbon plays a strengthening role in steel, controlling the carbon content can make the steel have a certain strength and hardness, phosphorus is a harmful element, it will reduce the toughness and plasticity of steel, strictly controlling the phosphorus content can improve the quality of steel. The temperature is set to 1610℃-1650℃ when tapping, and the appropriate tapping temperature can ensure the fluidity of the molten steel, which is convenient for the subsequent refining and pouring process.
[0033] At different stages of steel tapping, different proportions of deoxidizers are added to the molten steel to deoxidize the molten steel; specifically, after 1 / 6 of the steel is tapped, aluminum particles and carbon powder are added to the molten steel, and at this time, by mass percentage, aluminum particles: carbon powder = 1:5; after 1 / 2 of the steel is tapped, aluminum particles, carbon powder and metallic manganese are continued to be added to the molten steel, and at this time, by mass percentage, aluminum particles: carbon powder = 6:2. In this deoxidation process, an innovative "aluminum particles + carbon powder" mixture is used to deoxidize the converter steel. At different stages of the converter steel tapping, different ratios of aluminum particles and carbon powder are used to achieve safe and effective deoxidation to improve the strength and toughness of the steel.
[0034] After 5 / 6 of the steel is tapped, lime and pre-melted refined slag are added to the molten steel to desulfurize, dephosphorize, and remove inclusions. The amount of lime added is 4-5Kg / t, and the amount of pre-melted refined slag added is 3.5-4.5Kg / t.
[0035] As another innovative point of the present application, in the LF furnace refining of step S3, the aluminum content is controlled only when the LF furnace arrives at the station, and the aluminum-containing alloy and raw materials are restricted thereafter to control the aluminum content in the molten steel to change within a relatively low range. The specific method is to hoist the ladle into the LF furnace smelting station, start the ladle bottom blowing argon stirring, and the stirring time lasts for 3 minutes. After the stirring is completed, the LF furnace is powered on for 6-10 minutes for smelting. If the aluminum content in the molten iron is <0.015%, aluminum wire is fed into the molten steel. After the first sampling of aluminum content in the range of 0.015%-0.030%, it is prohibited to add any aluminum-containing raw materials to the molten steel. At this time, a deoxidizer is thrown on the slag surface of the ladle, and the deoxidizer is a mixture of calcium carbide and low-nitrogen carbon powder. Preferably, by mass percentage, calcium carbide: low-nitrogen carbon powder = 5:1; after the second sampling, the deoxidizer is continued to be thrown on the slag surface of the ladle, and the deoxidizer is high-purity silicon carbide; the entire LF refining time is controlled to be 40-50 minutes.
[0036] Then step S4: RH vacuum treatment, within 5 minutes of vacuum treatment, the vacuum degree is reduced to 60-80pa. Such low vacuum degree can create an environment conducive to removing gas and inclusions in molten steel. By reducing the pressure, the solubility of gas in molten steel is reduced, thereby promoting the escape of gas from molten steel. Continue to treat for 18 minutes to ensure that the gas and impurities in molten steel are fully removed and the purity of molten steel is improved. 60-100m nitrogen-manganese wire is fed into the molten steel. The nitrogen-manganese wire can provide the molten steel with an appropriate amount of nitrogen and manganese elements, so that the nitrogen content in the molten steel is relatively stable, which plays a role in adjusting the composition of molten steel and improving the strength and toughness of steel. At the same time, in order to prevent the uncontrollable modification process and the large-particle calcium aluminate inclusions generated thereby, it is forbidden to feed any inclusion modification wire into the molten steel. The soft blowing time is controlled at 15-20 minutes to ensure that the soft blowing effect is optimal, while avoiding excessive soft blowing that causes excessive temperature drop of molten steel or other adverse effects.
[0037] The LF refining in step S3 is combined with the RH vacuum refining in step S4 to intentionally control the aluminum content in the finished steel, and relatively weaken the effect of aluminum in refining the grains. The treatment is carried out under a specific vacuum degree for a specific time to stably control the nitrogen content in the molten steel after vacuum treatment, and then the grain size is refined by combining vanadium and nitrogen. Traditionally, nitrogen is restricted in anchor chains and anchor chain shackles because of concerns that nitrogen may cause steel embrittlement. However, when used in combination with vanadium, nitrogen can form stable carbonitrides with vanadium. These compounds not only do not cause embrittlement, but can play a role in refining grains and improving strength. For this reason, the idea of limiting nitrogen in traditional anchor chains and anchor chain shackles can be broken, and the advantages of vanadium-nitrogen alloys can be fully utilized to improve the performance of steel.
[0038] Step S5: continuous casting, the whole process protects casting, and the superheat range is set to 20-35°C; control the ratio of the amount of cold water to the electromagnetic stirring current of the crystallizer. The amount of cold water mainly affects the cooling rate of the billet in the crystallizer, while the electromagnetic stirring current of the crystallizer will affect the flow and solidification process of the molten steel. Reasonable control of the ratio of the two can ensure a good degree of segregation of the billet in the crystallizer and reduce the generation of surface and internal defects of the billet. Preferably, the ratio of the amount of cold water to the electromagnetic stirring current of the crystallizer is greater than 1:14. After the billet is cast, it is slowly cooled in the pit. The temperature during slow cooling in the pit is set to 650-720°C to reduce the thermal stress caused by excessive cooling, thereby reducing the risk of cracking of the billet. Set the pit exit temperature ≤100°C to further reduce the risk of deformation and cracking of the billet during subsequent processing and use.
[0039] The last step is step S6: rolling. The steel billet after slow cooling in step S5 is put into the furnace for rolling. The steel billet must be cold loaded into the furnace, and the heating temperature is set to 1180-1210℃. The steel billet after rolling continues to be slowly cooled in the pit, and the exit temperature is set to ≤100℃.
[0040] In order to further verify the scientific rationality of the large-size anchor chain shackle steel and the production method thereof provided by the present application, the present application provides three embodiments for verification, and at the same time provides a comparative example 1 for Example 1, a comparative example 2 for Example 2, and a comparative example 3 for Example 3, to further verify the advantages of the present application, which will be specifically elaborated below.
[0041] Example 1 and Comparative Example 1: The steel grade provided in Example 1 for processing large-size anchor chain shackles includes the following elements in percentage by mass: C 0.37%, Si 0.08%, Mn 1.60%, Cr 0.59%, Cu 0.04%, Ni 0.02%, Mo 0.038%, V0.052%, Nb 0.0035%, As 0.0023%, Al 0.010%, P 0.016%, S 0.0040%, B 0.0005%, Ti0.0030%, N 0.0068%, [O] 11ppm, [H] 1.2ppm, and the balance is Fe and unavoidable impurity elements; wherein Cr / Mo is controlled at 15.5.
[0042] The steel grade provided in Comparative Example 1 for processing large-size anchor chain shackles includes the following elements in percentage by mass: C 0.37%, Si 0.10%, Mn 1.62%, Cr 0.56%, Cu 0.03%, Ni 0.05%, Mo 0.021%, V0.055%, Nb 0.0040%, As 0.0038%, Al 0.008%, P 0.014%, S 0.0020%, B 0.0006%, Ti0.0020%, N 0.0065%, [O] 11ppm, [H] 1.2ppm, the balance is Fe and unavoidable impurity elements; Cr / Mo is controlled at 26.2.
[0043] The production method of large-size anchor chain shackle steel includes the following steps: The first step is to pretreat the molten iron. The KR mechanical stirring method is used to pretreat the molten iron for deep desulfurization. After the KR stirring is turned on for 1 minute, the desulfurizer is added to the stirring center. The sulfur content of the molten iron after deep desulfurization is controlled within 0.005%. After desulfurization, the desulfurization slag is scraped off.
[0044] The second step is the converter rough refining, which uses pre-treated molten iron and high-quality scrap steel (scrap steel produced in the factory) as smelting raw materials, and completes the rough refining in the converter. The converter endpoint control requirements are: C 0.14%, P 0.014%, and the tapping temperature is 1632℃. When tapping, after 16 tons of steel are tapped, aluminum particles + carbon powder (aluminum particles: carbon powder = 1:5) are added to the molten steel. After 50 tons of steel are tapped, aluminum particles + carbon powder (aluminum particles: carbon powder = 6:2) and metallic manganese are added to the molten steel. When the tapping amount is 83 tons, lime and pre-melted refining slag are added to the molten steel in sequence. The amount of lime added is 4Kg / t, and the amount of pre-melted refining slag added is 3.5Kg / t.
[0045] The third step is LF furnace refining. The ladle is hoisted into the LF furnace smelting station. According to the slag surface at the station, the ladle bottom blowing argon is started for stirring. The stirring is controlled within 3 minutes. After the stirring is completed, the power is turned on for 6-10 minutes. The aluminum content in the molten steel is 0.019%. The power is turned on for smelting. A mixture of calcium carbide and low-nitrogen carbon powder (calcium carbide: low-nitrogen carbon powder = 5:1) is sprinkled on the slag surface to achieve diffusion deoxidation. After the second refining sampling, the slag surface deoxidizer is changed to high-purity silicon carbide. The refining time is 44 minutes.
[0046] The fourth step is RH vacuum treatment. Within 5 minutes of vacuum treatment, the vacuum degree is reduced to 63 Pa. The treatment is carried out at this vacuum degree for 18 minutes. After the vacuum treatment, 70 m nitrogen-manganese wire is fed into the molten steel. It is forbidden to feed any inclusion-modified wire into the molten steel. The soft blowing time is controlled at 17 minutes.
[0047] The fifth step is continuous casting, using full-process protection casting, superheat 28°C, one cooling water volume: crystallizer electromagnetic stirring current = 1:13, the billet must enter the pit for slow cooling, the slow cooling temperature is 690°C, and the billet exit temperature is ≤100°C.
[0048] The sixth step is rolling. The billet must be cold loaded into the furnace. The cross-section of the billet is Ø500mm. The heating temperature is controlled at 1180~1210℃. The specification of the rolled steel is Ø180mm. The steel enters the pit and cools slowly. The temperature of the steel out of the pit is ≤100℃.
[0049] According to GB / T228.1 and GB / T229, tensile specimens and impact specimens are taken longitudinally at one-third of the radius of the round steel to test the mechanical properties; non-metallic inclusion specimens are taken at one-half of the radius to evaluate the purity of the round steel. The test results of Example 1 and Comparative Example 1 are shown in Table 1 and Table 2, respectively. It should be noted that the control of Cr / Mo has basically no effect on inclusions. Therefore, the non-metallic inclusion grade of Comparative Example 1 is not shown in Table 2. As an example, the present application also provides a test result diagram obtained in Example 1, that is, Figure 1 .
[0050] Table 1 Mechanical properties
[0051] Table 2 Non-metallic inclusions / grade
[0052] Example 2 and Comparative Example 2: The steel grade for processing large-size anchor chain shackles provided in Example 2 includes the following elements in mass percentage: C 0.37%, Si 0.07%, Mn 1.66%, Cr 0.61%, Cu 0.02%, Ni 0.01%, Mo 0.040%, V0.059%, Nb 0.0045%, As 0.0034%, Al 0.012%, P 0.014%, S 0.0030%, B 0.0004%, Ti0.0041%, N 0.0072%, [O] 9ppm, [H] 0.9ppm, and the balance is Fe and unavoidable impurity elements; wherein Cr / Mo is controlled at 15.25.
[0053] The steel grade for processing large-size anchor chain shackles provided in Comparative Example 2 includes the following elements in mass percentage: C 0.38%, Si 0.12%, Mn 1.65%, Cr 0.63%, Cu 0.03%, Ni 0.05%, Mo 0.030%, V0.061%, Nb 0.0060%, As 0.0051%, Al 0.015%, P 0.013%, S 0.0050%, B 0.0006%, Ti0.0035%, N 0.0064%, [O] 11ppm, [H] 1.2ppm, and the balance is Fe and unavoidable impurity elements; wherein Cr / Mo is controlled at 21.
[0054] The production method of large-size anchor chain shackle steel includes the following steps: The first step is to pretreat the molten iron. The KR mechanical stirring method is used to pretreat the molten iron for deep desulfurization. After the KR stirring is turned on for 1 minute, the desulfurizer is added to the stirring center. The sulfur content of the molten iron after deep desulfurization is controlled within 0.005%. After desulfurization, the desulfurization slag is scraped off.
[0055] The second step is the converter rough refining, which uses pre-treated molten iron and high-quality scrap steel (self-produced scrap steel in the factory) as smelting raw materials, and completes the rough refining in the converter. The converter endpoint control requirements are: C 0.16%, P 0.011%, and the tapping temperature is 1639℃. When tapping, after 16 tons of steel are tapped, aluminum particles + carbon powder (aluminum particles: carbon powder = 1:5) are added to the molten steel. After 50 tons of steel are tapped, aluminum particles + carbon powder (aluminum particles: carbon powder = 6:2) and metallic manganese are added to the molten steel. When the tapping amount is 83 tons, lime and pre-melted refining slag are added to the molten steel in sequence. The amount of lime added is 4Kg / t, and the amount of pre-melted refining slag added is 3.5Kg / t.
[0056] The third step is LF furnace refining. The ladle is hoisted into the LF furnace smelting station. According to the slag surface at the station, the ladle bottom blowing argon stirring is started. The stirring is controlled within 3 minutes. After the stirring is completed, the power is turned on for 6-10 minutes. The aluminum content in the molten steel is 0.020%. The power is turned on for smelting. A mixture of calcium carbide and low-nitrogen carbon powder (calcium carbide: low-nitrogen carbon powder = 5:1) is sprinkled on the slag surface to achieve diffusion deoxidation. After the second refining sampling, the slag surface deoxidizer is changed to high-purity silicon carbide. The refining time is 46 minutes.
[0057] The fourth step is RH vacuum treatment. Within 5 minutes of vacuum treatment, the vacuum degree is reduced to 65 Pa. The treatment is carried out at this vacuum degree for 18 minutes. After the vacuum treatment, 75 m nitrogen-manganese wire is fed into the molten steel. It is forbidden to feed any inclusion-modified wire into the molten steel. The soft blowing time is controlled at 19 minutes.
[0058] The fifth step is continuous casting, which uses full-process protection casting, superheat of 30°C, the amount of cold water: the electromagnetic stirring current of the crystallizer = 1:13, the billet must be slowly cooled in the pit, the slow cooling temperature is 700°C, and the billet exit temperature is ≤100°C.
[0059] The sixth step is rolling. The billet must be cold loaded into the furnace. The cross-section of the billet is Ø500mm. The heating temperature is controlled at 1180-1210℃. The specification of the rolled steel is Ø250mm. The steel enters the pit and cools slowly. The temperature of the steel out of the pit is ≤100℃.
[0060] According to GB / T228.1 and GB / T229, tensile specimens and impact specimens are taken longitudinally at one-third of the radius of the round steel to test the mechanical properties; non-metallic inclusion specimens are taken at one-half of the radius to evaluate the purity of the round steel. The specific test results of Example 2 and Comparative Example 2 are shown in Table 3 and Table 4, respectively. It should be noted that the control of Cr / Mo has basically no effect on inclusions. Therefore, the non-metallic inclusion grade of Comparative Example 2 is not displayed in Table 4. As an example, the present application also provides a test result diagram obtained in Example 2, that is, Figure 2 .
[0061] Table 3 Mechanical properties
[0062] Table 4 Non-metallic inclusions / grade
[0063] Example 3 and Comparative Example 3: The steel grade provided in Example 3 for processing large-size anchor chain shackles includes the following elements in percentage by mass: C 0.34%, Si 0.12%, Mn 1.67%, Cr 0.63%, Cu 0.04%, Ni 0.04%, Mo 0.044%, V0.066%, Nb 0.0065%, As 0.0037%, Al 0.014%, P 0.017%, S 0.005%, B 0.0003%, Ti0.0048%, N 0.0072%, [O] 7ppm, [H] 1.0ppm, and the balance is Fe and unavoidable impurity elements; wherein Cr / Mo is controlled at 14.32.
[0064] The steel grade for processing large-size anchor chain shackles provided in Comparative Example 3 includes the following elements in mass percentage: C 0.35%, Si 0.09%, Mn 1.61%, Cr 0.61%, Cu 0.01%, Ni 0.04%, Mo 0.025%, V0.059%, Nb 0.0057%, As 0.0049%, Al 0.016%, P 0.011%, S 0.0020%, B 0.0002%, Ti0.0036%, N 0.0070%, [O] 11ppm, [H] 1.2ppm, and the balance is Fe and unavoidable impurity elements; wherein Cr / Mo is controlled at 24.4.
[0065] The production method of large-size anchor chain shackle steel includes the following steps: The first step is to pretreat the molten iron. The KR mechanical stirring method is used to pretreat the molten iron for deep desulfurization. After the KR stirring is turned on for 1 minute, the desulfurizer is added to the stirring center. The sulfur content of the molten iron after deep desulfurization is controlled within 0.005%. After desulfurization, the desulfurization slag is scraped off.
[0066] The second step is the converter rough refining, which uses pre-treated molten iron and high-quality scrap steel (scrap steel produced in the factory) as smelting raw materials and completes the rough refining in the converter. The converter endpoint control requirements are: C 0.14%, P 0.015%, and the tapping temperature is 1640℃. When tapping, after 16 tons of steel are tapped, aluminum particles + carbon powder (aluminum particles: carbon powder = 1:5) are added to the molten steel. After 50 tons of steel are tapped, aluminum particles + carbon powder (aluminum particles: carbon powder = 6:2) and metallic manganese are added to the molten steel. When the tapping amount is 83 tons, lime and pre-melted refining slag are added to the molten steel in sequence. The amount of lime added is 4.5Kg / t, and the amount of pre-melted refining slag added is 4Kg / t.
[0067] The third step is LF furnace refining. The ladle is hoisted into the LF furnace smelting station. According to the slag surface at the station, the ladle bottom blowing argon stirring is started. The stirring is controlled within 3 minutes. After the stirring is completed, the power is turned on for 6-10 minutes. The aluminum content in the molten steel is 0.013%. 20m of aluminum wire is fed into the molten steel, and the power is turned on for smelting. A mixture of calcium carbide and low-nitrogen carbon powder (calcium carbide: low-nitrogen carbon powder = 5:1) is sprinkled on the slag surface to achieve diffusion deoxidation. After the second refining sampling, the slag surface deoxidizer is changed to high-purity silicon carbide. The refining time is 46 minutes.
[0068] The fourth step is RH vacuum treatment. Within 5 minutes of vacuum treatment, the vacuum degree is reduced to 68 Pa. The treatment is carried out at this vacuum degree for 18 minutes. After the vacuum treatment, 80 m of nitrogen-manganese wire is fed into the molten steel. It is forbidden to feed any inclusion-modified wire into the molten steel. The soft blowing time is controlled at 16 minutes.
[0069] The fifth step is continuous casting, using full-process protection casting, superheat 27°C, one cooling water volume: crystallizer electromagnetic stirring current = 1:13, the billet must enter the pit for slow cooling, the slow cooling temperature is 700°C, and the billet exit temperature is ≤100°C.
[0070] The sixth step is rolling. The billet must be cold loaded into the furnace. The cross-section of the billet is Ø500mm. The heating temperature is controlled at 1180-1210℃. The specification of the rolled steel is Ø300mm. The steel enters the pit and cools slowly. The temperature of the steel out of the pit is ≤100℃.
[0071] According to GB / T228.1 and GB / T229, tensile specimens and impact specimens are taken longitudinally at one-third of the radius of the round steel to test the mechanical properties; non-metallic inclusion specimens are taken at one-half of the radius to evaluate the purity of the round steel. The test results of Example 3 and Comparative Example 3 are shown in Tables 5 and 6, respectively. It should be noted that the control of Cr / Mo has basically no effect on inclusions. Therefore, the non-metallic inclusion grade of Comparative Example 3 is not displayed in Table 6. As an example, the present application also provides a test result diagram obtained in Example 3, that is, Figure 3 .
[0072] Table 5 Mechanical properties
[0073] Table 6 Non-metallic inclusions / grade
[0074] It can be seen from the above-mentioned Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, Example 3 and Comparative Example 3 and comparative examples that the steel used for processing large-size anchor chain shackles obtained by the present application has a lower yield strength of 608-650Mpa, a tensile strength of 750-790Mpa, an elongation of 22.3-25%, a cross-sectional shrinkage of 67-72%, a 0°C V-type impact energy of 118-162J, non-metallic inclusions of Class A ≤0.5 grade, Class B ≤0.5 grade, Class D ≤1.0 grade, and Class C is Class 0; at the same time, specific control of Cr / Mo can effectively suppress the brittle phenomenon of tempering after quenching, so that the impact energy is guaranteed, and finally the requirements of the mechanical properties of the steel are met.
[0075] At the same time, after cost calculation, this type of steel has a very high cost-effectiveness and can completely replace existing products.
[0076] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art to which this application belongs. It should also be understood that terms such as those defined in common dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless defined as herein.
[0077] The meaning of "and / or" described in this application means that the situations where each exists alone or both exist at the same time are included.
[0078] The term “connection” as used in this application may mean a direct connection between components or an indirect connection between components via other components.
[0079] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A large-size anchor chain shackle steel, characterized by: For steel grades used for processing large-size anchor chain shackles with a diameter of Ø≥180mm, the steel grades include the following elements in mass percentage: C: 0.34-0.38%, Si: 0.05-0.12%, Mn: 1.58-1.68%, Cr: 0.56-0.65%, Cu≤0.10%, Ni≤0.08%, Mo: 0.035-0.045%, V: 0.050-0.070%, Nb≤0.0080%, As≤0.0050%, Al: 0.005-0.020%, P≤0.018%, S≤0.005%, B≤0.0006%, Ti≤0.0050%, N: 0.0060-0.080%, [O]≤20ppm, [H]≤2ppm, and the balance is Fe and unavoidable impurity elements; Cr / Mo is controlled at 12-19.
2. The large-size anchor chain shackle steel according to claim 1 is characterized by: If the diameter of the steel used for processing large-size anchor chain shackles is 180mm≤Ø≤240mm, it includes the following elements in mass percentage: C: 0.36-0.38%, Si: 0.05-0.12%, Mn: 1.58-1.64%, Cr: 0.56-0.60%, Cu≤0.10%, Ni≤0.08%, Mo: 0.035-0.045%, V: 0.050-0. 060%, Nb≤0.0080%, As≤0.0050%, Al: 0.005-0.020%, P≤0.018%, S≤0.005%, B≤0.0006%, Ti≤0.0050%, N: 0.0060-0.080%, [O]≤20ppm, [H]≤2ppm, the balance is Fe and unavoidable impurity elements; Cr / Mo is controlled at 12-18.
3. The large-size anchor chain shackle steel according to claim 1 is characterized by: If the diameter of the steel used for processing large-size anchor chain shackles is 180mm<Ø≤270mm, it includes the following elements in mass percentage: C: 0.34-0.37%, Si: 0.05-0.12%, Mn: 1.62-1.67%, Cr: 0.58-0.63%, Cu≤0.10%, Ni≤0.08%, Mo: 0.035-0.045%, V: 0.055-0. 065%, Nb≤0.0080%, As≤0.0050%, Al: 0.005-0.020%, P≤0.018%, S≤0.005%, B≤0.0006%, Ti≤0.0050%, N: 0.0060-0.080%, [O]≤20ppm, [H]≤2ppm, the balance is Fe and unavoidable impurity elements; Cr / Mo is controlled at 12-18.
4. The large-size anchor chain shackle steel according to claim 1 is characterized by: If the diameter of the steel used for processing large-size anchor chain shackles is 270mm<Ø≤300mm, it includes the following elements in mass percentage: C: 0.34-0.36%, Si: 0.05-0.12%, Mn: 1.63-1.68%, Cr: 0.60-0.65%, Cu≤0.10%, Ni≤0.08%, Mo: 0.035-0.045%, V: 0.060-0. 070%, Nb≤0.0080%, As≤0.0050%, Al: 0.005-0.020%, P≤0.018%, S≤0.005%, B≤0.0006%, Ti≤0.0050%, N: 0.0060-0.080%, [O]≤20ppm, [H]≤2ppm, the balance is Fe and unavoidable impurity elements; Cr / Mo is controlled at 13-19.
5. The method for producing large-size anchor chain shackle steel according to claim 2, 3 or 4, characterized in that: The specific steps include: Step S1: pretreatment of molten iron: mechanical stirring is used to pretreatment the molten iron for desulfurization. After starting the stirring for 1 minute, a desulfurizer is added to the molten iron. The sulfur content after pretreatment is ≤0.005%, and the desulfurization slag is scraped off; Step S2: rough refining in a converter, adding high-quality scrap steel to the molten iron pretreated in step S1, the smelting end point includes the following elements in mass percentage: C ≥ 0.10%, P ≤ 0.018%, and the temperature when tapping is 1610°C-1650°C; Deoxidizers of different proportions are added to the molten steel at different stages of steel tapping to deoxidize the molten steel; lime and pre-melted refined slag are added during steel tapping to remove inclusions in the molten steel; Step S3: LF furnace refining, hoisting the ladle into the LF furnace smelting station, starting the ladle bottom blowing argon stirring, setting the stirring time, after the stirring is completed, the LF furnace is powered on for smelting, setting the smelting time, if the aluminum content in the molten iron is less than 0.015%, feeding aluminum wire into the molten steel, after the first sampling aluminum content is within the range of 0.015%-0.030%, throwing a deoxidizer on the slag surface of the ladle, the deoxidizer is a mixture of calcium carbide and low-nitrogen carbon powder; after the second sampling, continue to throw a deoxidizer on the slag surface of the ladle, the deoxidizer is high-purity silicon carbide; Step S4: RH vacuum treatment, reducing the vacuum degree to within a preset range, continuing the treatment for a preset time, feeding nitrogen-manganese wire into the molten steel, and performing soft blowing at the same time; Step S5: continuous casting, the whole process is protected, the superheat range is set to 20-35°C, and the ratio of the amount of cold water and the electromagnetic stirring current of the crystallizer is controlled; after the steel billet is cast, it is slowly cooled in the pit, and the exit temperature is set to ≤100°C; Step S6: rolling. The steel billet after slow cooling in step S5 is put into the furnace for rolling. The heating temperature is set to 1180-1210°C. The steel billet after rolling continues to be slowly cooled in the pit, and the exit temperature is set to ≤100°C.
6. The method for producing large-size anchor chain shackle steel according to claim 5, characterized in that: In step S2, different proportions of deoxidizer are added to the molten steel at different stages of steel tapping to deoxidize the molten steel. Specifically, after 1 / 6 of the steel is tapped, aluminum particles and carbon powder are added to the molten steel. At this time, the ratio of aluminum particles to carbon powder is 1:5 by mass percentage. After 1 / 2 of the steel is tapped, aluminum particles, carbon powder and metallic manganese are added to the molten steel. At this time, the mass percentage of aluminum particles: carbon powder is 6:2; After 5 / 6 of the steel is tapped, lime and pre-melted refined slag are added to the molten steel. The amount of lime added is 4-5 kg / t, and the amount of pre-melted refined slag added is 3.5-4.5 kg / t.
7. The method for producing large-size anchor chain shackle steel according to claim 5, characterized in that: In step S3, after the ladle is hoisted into the LF furnace smelting station, argon blowing and stirring are started at the bottom of the ladle for 3 minutes. After the stirring is completed, the LF furnace is powered on for 6-10 minutes for smelting; after the first sampling, the deoxidizer added is a mixture of calcium carbide and low-nitrogen carbon powder, and the mass percentage is calcium carbide: low-nitrogen carbon powder = 5:1; the entire LF refining time is controlled to be 40-50 minutes.
8. The method for producing large-size anchor chain shackle steel according to claim 5, characterized in that: In step S4, within 5 minutes of vacuum treatment, the vacuum degree is reduced to 60-80 Pa, and the treatment is carried out at this vacuum degree for 18 minutes; after the vacuum treatment, 60-100 m nitrogen-manganese wire is fed into the molten steel, and the soft blowing time is controlled at 15-20 minutes.
9. The method for producing large-size anchor chain shackle steel according to claim 5, characterized in that: In step S5, when the overheating range is 20-35°C, the ratio of the amount of cold water to the electromagnetic stirring current of the crystallizer is greater than 1:14, and the temperature of the cast billet when entering the pit for slow cooling is set to 650-720°C.
10. The method for producing large-size anchor chain shackle steel according to claim 5, characterized in that: The steel grade for processing large-size anchor chain shackles produced by the production method has a lower yield strength of 608-650 MPa, a tensile strength of 750-790 MPa, an elongation of 22.3-25%, a cross-sectional shrinkage of 67-72%, a 0°C V-type impact energy of 118-162 J, and non-metallic inclusions of Class A ≤0.5, Class B ≤0.5, Class D ≤1.0, and Class C 0.
Citation Information
Patent Citations
Manufacturing method for double-nut D type connecting shackle
CN105880950A
Kenter shackle
CN109073044A
Antifatigue R6 connecting shackle and forging method thereof
CN111015092A
Manufacturing technology of R6-level Kenter shackle
CN111468889A
High-strength D-shaped shackle
CN217323017U